Tuvan literature under the Tuvan People’s Republic: The birth of the poetics of artistic modality - Dongak, Uran A. (The New Research of Tuva, 2020)
The article analyses the history of the origin of Tuvan national literature during the period of the Tuvan People’s Republic (1921–1944). We have traced the process of transition from traditionalism (folklore consciousness) to individual author's creativity in the main categories of historical poetics, which are that of genre, author and style. The article also identifies the poetics of artistic modality as the initial stage of the literary consciousness in the context of historical time.One of the first Tuvan literary publications “Cььndь cogaaldar” (“Selected works”) contains diversely constructed texts, such as pieces of folk songs in canonical form, collective songs of revolutionary content (arats’ songs) and works which had specific individual authors, as well as slogan poems. Tuvan literature of the 1930s still uses traditional poetics, but the poetics of artistic modality is already being actualized.
Keywords: Tuva; Tuvan People’s Republic; Tuvan history; Tuvan literature; Tuvan language; Tuvan poetry; historical poetics; traditional poetics; poetics of artistic modality; arats’ song; slogan poem; shuluk